Asociación entre sobrepeso/obesidad y depresión en estudiantes de medicina - Paredes Muñoz, Martin Abel (2022)
Depression is a mental disorder that affects people's quality of life just like obesity affects millions of people. A causal relationship between obesity and depression has been established, with diseases predisposing one to the other. Objective: To determine if there is an association between overweight / obesity and depression in medical students Materials and methods: A PQH-9 survey on depression was conducted with 235 students from the Faculty of Medicine of the National University of Trujillo (UNT) and anthropometric measurements were performed. Results: The average age of the surveyed students was between 21-25 years, depression in this population group had a frequency of 66.8% and those with overweight / obesity was 52.34%. Conclusions: There is an association between overweight / obesity and depression, finding a Relative Risk of 1.32 with IC 95% [1.09-1.59].